FAKTOR-FAKTOR YANG MEMPENGARUHI TAX AVOIDANCE PADA PERUSAHAAN SEKTOR CYCLICALS DAN NON-CYCLICALS - Lekoy, Yoel Dwijaya; Lasar, Hilary Flora A. T. (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
The purpose of this study is to obtain empirical evidence regarding the influence of capital intensity, corporate social responsibility, profitability, leverage, deferred tax expense, and audit committees on tax avoidance. The research focuses on companies in the cyclical and non-cyclical sectors listed on the Indonesia Stock Exchange during the period from 2020 to 2022, with 61 companies meeting the research criteria and a total of 183 data points as the research sample. Purposive sampling was employed for sample selection, and regression analysis using SPSS software was utilized for data analysis. The independent variables in this study include capital intensity, corporate social responsibility, profitability, deferred tax expense, and audit committees, while tax avoidance serves as the dependent variable. The results of this study indicate that capital intensity, corporate social responsibility, deferred tax expense, and audit committees do not have a significant influence on tax avoidance. However, profitability, using return on assets as a proxy, exhibits a negative influence on tax avoidance.